Properties of titanium thin film deposited by RF and DC magnetron sputtering at low temperatures - Chiyun Bang; Ju-Hong Cha (AIP Advances, 2025)
Ti thin films with superior surface properties are deposited in a low-temperature processing environment. The properties of Ti films deposited by magnetron sputtering at substrate temperatures below 200 °C and different RF (radio frequency, 13.56 MHz) and DC (direct current) powers were examined. In an Ar gas environment, the deposition rate, surface roughness, and resistivity of the Ti thin films deposited on Si substrates were analyzed under various conditions, including the applied power (200–600 W), process pressure (1–10 mTorr), and substrate temperature (room temperature to 180 °C). DC magnetron sputtering has a high deposition rate for the fabrication of low-temperature Ti thin films because of the strong electric field formed at the cathode surface. In contrast, RF sputtering generates a high ion density in the bulk region, owing to the unique properties of RF plasma, while simultaneously improving the surface properties through the relatively high incident ion energy at the substrate. In a low-temperature processing environment, RF magnetron sputtering produces high-quality thin films with superior characteristics, including lower surface roughness and lower resistivity, compared to DC magnetron sputtering.